STRATEGI PELATIHAN KARYAWAN PADA PD BARAMARTA MARTAPURA - Hikmayanti Huwaida (Islamic University of Kalimantan MAB Banjarmasin, 2017)
The purpose of this research is to discover the importance of training and good training strategy for employees at PD Baramarta Martapura. Data and information obtained using descriptive analysis. The results shows, unproductive employees caused by the less knowledge and ability to run the production machine. The right strategy is to do the training stages consist of setting goals, developing curriculum, determining training facilities, selecting trainees, appointing trainers and determining the training implementation schedule. Keywords: Strategy, Training, Productive, Employee.